Process and Product Characterization of Aliha, A Maize-Based Ghanaian Indigenous Fermented Beverage - Felix Kwashie Madilo; Angela Parry-Hanson Kunadu; Kwaku Tano-Debrah; Gloria Ivy Mensah; Kwesi Firibu Saalia; Unathi Kolanisi (Journal of Food Quality)
Aliha is a maize-based traditional fermented beverage prepared and consumed in Ghana, predominantly in the Volta Region and other parts of Ghana. The study sought to characterize the production processes, the nutritional values, and microbial composition of aliha. A total of 126 aliha producers in the Volta, Greater Accra, and Ashanti Regions were sampled using snowballing to identify and to recruit the producers for the study, using a pretested self-administered questionnaire. The physicochemical and microbial composition were carried out using standard methods. Four different production techniques were identified across the production sites. The variations identified during the production existed across the production chain. The main ingredients used for aliha production are corn, caramel, sugar, and water. However, aliha produced by the ‘original’ method (DN2) presented the best nutritional values (proteins, energy, and calcium), followed by backslopping techniques, AG1 (total carbohydrates and ash), and AG2 (fats and oils and phosphorus). Fungi and Enterobacteriaceae dominated the initial fermentation stages (24 h) with low acid values. However, as the fermentation time increased from 24 h to 72 h, the acid contents of the fermenting beverage increased sharply leading to a drastic reduction of fungi and Enterobacteriaceae contents with increasing records of lactic acid bacterial counts. Even though DN2 presented the best nutritional values, it was highly contaminated. Hence, the producers must be encouraged to use backslopping techniques for safety and to shorten the duration of production.